Treinamento de segurança do trabalho na indústria: comparação entre os métodos de realidade virtual e tradicional em sala de aula - Vieira, Leandro Roberto Vaz (2022)
The application of occupational safety training and risks in the work environment is a challenge for organizations around the world. To lessen these risks and replace traditional training models, organizations are adopting innovative approaches such as virtual reality (VR). Studies show the potential that VR, such as increase student motivation and engagement, as it can achieve knowledge retention results in the learning process after training, unlike the traditional classroom method. However, the analyzed studies did not measure knowledge retention over long periods after the end of training. Therefore, the objective of this study is to evaluate the evolution of knowledge retention when applying occupational safety training to employees of an automobile industry, comparing the methods of virtual reality and traditional in the classroom. For this, we used quantitative and qualitative methods, to compare the experimental and the control groups. The statistical results showed that the VR method is more effective in terms of practical learning of some content, such as 5S and Work Instruction, and equally effective in terms of theoretical learning about the content of personal protective equipment (PPE). The results of the thematic analysis of the experiment also presented benefits such as: knowledge retention, behavioral effects, and technological advances. As for the challenges, the following were obtained: user-technology interaction, physical integrity relationship, organizational infrastructure, and technological limitation. Additionally, the use of VR systems in safety training improves employee engagement and satisfaction.